2012
DOI: 10.1002/hep.25699
|View full text |Cite
|
Sign up to set email alerts
|

Histone deacetylase 6 functions as a tumor suppressor by activating c-Jun NH2-terminal kinase-mediated beclin 1-dependent autophagic cell death in liver cancer

Abstract: Ubiquitin-binding histone deacetylase 6 (HDAC6) is uniquely endowed with tubulin deacetylase activity and plays an important role in the clearance of misfolded protein by autophagy. In cancer, HDAC6 has become a target for drug development due to its major contribution to oncogenic cell transformation. In the present study we show that HDAC6 expression was down-regulated in a large cohort of human hepatocellular carcinoma (HCC) patients, and that low expression of HDAC6 was significantly associated with poor p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
86
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 94 publications
(93 citation statements)
references
References 27 publications
4
86
1
2
Order By: Relevance
“…S1C). In addition, we performed GSEA using three different cancer cell lines (liver, lung, and gastric cancer) to confirm HDAC2 signatures in these cell lines (7,9,10). Indeed, GSEA showed that EGFR system-related gene elements were commonly enriched in HDAC2 signatures observed in these cell lines (Fig.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…S1C). In addition, we performed GSEA using three different cancer cell lines (liver, lung, and gastric cancer) to confirm HDAC2 signatures in these cell lines (7,9,10). Indeed, GSEA showed that EGFR system-related gene elements were commonly enriched in HDAC2 signatures observed in these cell lines (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…S1A). Because the mRNA and protein levels of HDAC2 were upregulated in overt hepatocellular carcinoma, we next assessed the prognostic implications of HDAC2 expression in a large cohort of patients with hepatocellular carcinoma described in our previous study (10). First, 3,039 genes with expression patterns highly correlated with HDAC2 expression were selected for cluster analysis (P < 0.05, r > 0.4 or r < À0.4; Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly variable results on HDAC6 expression levels have been published for hepatocellular cancers. 27,37,38 Furthermore, HDAC6 has been reported to stimulate proliferation in the latter tumor type. In breast cancer, HDAC6 expression was likewise variable 29 and particularly strong in small tumors with low histological grade.…”
Section: Discussionmentioning
confidence: 99%
“…52,53 In liver cancer, HDAC6 did not affect proliferation, too, but regulated autophagy. 38 Similarly, the newly developed HDAC6-specific inhibitor C1A generated a significant growth inhibitory effect across a number of different cancer cell lines by induction of apoptosis rather than cell cycle arrest, in contrast to the effect of the pan-HDAC inhibitor SAHA. 51 Our findings showing only a moderate induction of apoptosis after inhibition of enzyme activity with even higher concentrations of Tubacin, but no induction of apoptosis after diminution of protein expression by siRNA knockdown, indicate that neither HDAC6 protein expression nor enzymatic activity are critical for urothelial carcinoma cells in general.…”
Section: Discussionmentioning
confidence: 99%